Best Practice Recommendations for Stroke Patients with Dysphagia: A Delphi-Based Consensus Study of Experts in Turkey-Part II: Rehabilitation - (:unkn) unknown (SPRINGER, 2021)
Dysphagia is one of the most common and important complications of stroke. It is an independent marker of poor outcome following acute stroke and it continues to be effective for many years. This consensus-based guideline is not only a good address to clinical questions in practice for the clinical management of dysphagia including management, diagnosis, follow-up, and rehabilitation methods, but also includes detailed algorithms for these topics. The recommendation paper has been written by a multidisciplinary team and offers 117 recommendations for stroke patients with dysphagia. While focusing on management principles, diagnosis, and follow-up in the 1st part (45 items), rehabilitation details were evaluated in the 2nd part (72 items).
Keywords: Dysphagia; Stroke; Recommendation; Delphi study; Rehabilitation; HEALTH-CARE PROFESSIONALS; NEUROMUSCULAR ELECTRICAL-STIMULATION; NONINVASIVE BRAIN-STIMULATION; RESPIRATORY MUSCLE STRENGTH; ACUTE ISCHEMIC-STROKE; CHIN TUCK; OROPHARYNGEAL DYSPHAGIA; POSTSTROKE DYSPHAGIA; ENTERAL NUTRITION; SUBACUTE STROKE